A AgX / Ag composite metal organic framework material and its preparation method and application
Through the design of Cu(I)MOFs-AgX/Ag composite material, the problem of easy aggregation and light decomposition of silver-based materials is solved, and efficient antibacterial and antiviral effects are achieved, especially under light conditions, the ability to kill bacteria and viruses is significantly improved.
Patent Information
- Application Number
- CN202211472430.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-11-23
AI Technical Summary
The existing silver-based materials are prone to aggregation, light decomposition and other inactivation, resulting in poor antibacterial and antiviral effects.
Cu(I)MOFs-AgX/Ag composite metal organic frame material is used. This material fixes silver ions through Cu(I)MOFs skeleton and halogen ion clusters, grows AgX nanoparticles in situ, form AgX/Ag heterostructures, avoid silver particles aggregation, and uses the photoresponsive characteristics of MOFs to enhance antibacterial and antiviral activity.
The stability of silver-based materials and the antibacterial and antiviral effects have been improved, especially under light conditions, showing enhanced killing effects on bacteria and viruses.
Smart Images

Figure CN116144033B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal organic framework material, in particular to an AgX / Ag composite metal organic framework material and a preparation method and application thereof. Background Art
[0002] Bacterial infection has always been an important issue of concern in the fields of global public health, food safety and the environment. Antibiotics are currently the main method for treating bacteria. However, problems such as drug resistance caused by the abuse of antibiotics and the emergence of superbugs are becoming increasingly prominent.
[0003] Currently, most physical disinfection methods often require special equipment and energy; chemical disinfectants may produce toxic gases during their application, which can also harm the human body, corrode metals or damage the environment.
[0004] Different from traditional chemical disinfectants and physical disinfection methods, inorganic nano-disinfection materials have good safety, stability and sustainability, and do not cause secondary pollution, and have broad application prospects.
[0005] Silver-based materials have a certain application history as antibacterial and antiviral media, especially nano-sized silver has better antibacterial and antiviral activity. Silver can release silver ions to produce a bactericidal effect. As a plasmon particle, its surface plasma resonance effect gives silver materials good photocatalytic activity and has good photocatalytic enhanced antibacterial and antiviral application potential. Silver halogen compounds are a kind of semiconductor material. When combined with metallic silver, they can form an inhibitory structure, expand its light absorption range and enhance the bactericidal effect. The material still has the key problem of unstable structure and easy aggregation to form large particles and inactivation.
[0006] Metal-organic frameworks (MOFs) are porous crystalline materials formed by the assembly of inorganic metal / non-metallic particle clusters and organic ligands. They have a multi-component, ordered pore structure, and rich physical and chemical functionalities, making them a new generation of antibacterial and antiviral media materials. The permanent pore structure of the MOFs framework can be used as a nano-reaction cavity to control the size growth of inorganic nanoparticles, and can control the preparation of silver nanoparticles with specific nano-sizes. The new material composed of MOFs materials and silver-based nanoparticles can avoid the reduction of activity caused by the aggregation of silver particles, control the release of active components, and also use the light response characteristics of MOFs to enhance the antibacterial and antiviral activity of the composite material.
[0007] Chinese patent CN202011181167.4 discloses a silver-based metal organic framework material and its preparation method and application. A silver-based MOFs is designed and synthesized by solvent evaporation method using Ag ions, pyridine and pyrenesulfonic acid. The large π bonds in pyrenesulfonic acid form a stacked two-dimensional structure that is conducive to the formation of excitons, making singlet oxygen the main active species and ensuring the stability of Ag ions. However, it forms silver-based MOFs, which cannot play the role of silver halogen compounds, and has not been proven to have antibacterial and antiviral effects.
[0008] The present invention aims to solve the defects of the prior art that silver-based materials are easy to aggregate, decompose under light and become inactive, and to provide a highly efficient photocatalytic antibacterial and antiviral material. Summary of the invention
[0009] The purpose of the present invention is to provide an AgX / Ag composite metal organic framework material and its preparation method and application in order to solve at least one of the above problems, so as to solve the defects of silver-based materials in the prior art such as easy aggregation, light decomposition and easy inactivation, and achieve efficient antibacterial and antiviral effects.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] The first aspect of the present invention discloses an AgX / Ag composite metal organic framework material, which is Cu(Ⅰ)MOFs-AgX / Ag, wherein X is a halogen;
[0012] Cu(Ⅰ)MOFs are formed by the assembly of cuprous metal-halogen ion clusters and 4,4'-bipyridine molecules, and the halogen ions are used to anchor silver ions. In the process, AgX is grown in situ and metallic Ag nanoparticles are derived, thus forming a Cu(Ⅰ)MOFs-AgX / Ag heterostructure material. Taking halogen chloride as an example, the final material formed is Cu(Ⅰ)MOFs-AgCl / Ag.
[0013] Preferably, in the Cu(Ⅰ)MOFs-AgX / Ag, the ratio of silver element to copper element is 0.25-2:1.
[0014] Preferably, the Cu(Ⅰ)MOFs-AgX / Ag particle size distribution is 0.5-2 μm.
[0015] The second aspect of the present invention discloses a method for preparing any of the above-mentioned AgX / Ag composite metal organic framework materials, comprising the following steps:
[0016] S1: MOFs preparation:
[0017] S11: adding a cuprous halogen compound to a solvent and stirring at room temperature;
[0018] S12: dissolving 4,4'-bipyridine molecules in a solvent, adding the 4,4'-bipyridine molecules to the solution obtained in step S11 after they are fully dissolved, and continuing to stir;
[0019] S13: separating the MOFs solid in the solution obtained in step S12 by centrifugation, washing it twice by centrifugation with anhydrous ether, and vacuum drying it to obtain a MOFs material;
[0020] S2: Preparation of Cu(Ⅰ)MOFs-AgX / Ag:
[0021] S21: dissolving a silver ion source in anhydrous ethanol to form a silver ethanol solution;
[0022] S22: weigh the MOFs material obtained in step S13 and add it to the silver ethanol solution obtained in step S21, disperse it by ultrasonic wave and then stir it;
[0023] S23: The solid sample in the solution obtained in step S12 is centrifuged and washed twice by centrifugation with ethanol, and then vacuum dried to obtain Cu(I)MOFs-AgX / Ag.
[0024] Preferably, the cuprous halogen compound is selected from cuprous chloride, cuprous bromide or cuprous iodide; the solvent is acetonitrile; cuprous halogen compound: 4,4'-bipyridine molecule: solvent = 5 mmol: 5 mmol: 60 mL.
[0025] Preferably,
[0026] The stirring time in step S11 is 10 min;
[0027] The stirring time in step S12 is 30 min;
[0028] The centrifugal speed in step S13 is 7000 rpm, the time is 10 min, and the vacuum drying temperature is 60° C., the time is 24 h.
[0029] Preferably, the silver ion source is silver nitrate; silver ion source: MOFs material: anhydrous ethanol = 10-80 mg: 50 mg: 15 mL.
[0030] Preferably,
[0031] The stirring time in step S22 is 1-12h;
[0032] The vacuum drying in step S23 is carried out at a temperature of 60° C. and for a period of 24 hours.
[0033] The third aspect of the present invention discloses an application of any of the above-mentioned AgX / Ag composite metal organic framework materials in the field of antibacterial and antiviral.
[0034] Preferably, the photocatalytic enhancement of Cu(I)MOFs-AgX / Ag has antibacterial and antiviral effects.
[0035] The principle of the present invention is:
[0036] The copper (I) MOFs framework and halogen ion clusters are used as the fixing sites of silver ions, and AgX nanoparticles are formed in situ in the MOFs pore cavity. The distribution of AgX nanoparticles is controlled by the framework structure and fixed in the pore structure. During the reaction, metallic Ag is derived to form AgX / Ag heterostructure particles, and finally Cu(I) MOFs-AgX / Ag composite materials are formed. The MOFs material assembled by cuprous halide and 4,4'-bipyridine has photosensitivity and can act as a photocatalyst to cooperate with AgX / Ag nanoparticles to enhance the antibacterial and antiviral effects.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The present invention uses MOFs nanomaterials prepared by stirring at room temperature. The preparation process of the material has the characteristics of simple method, mild reaction conditions, and easy scale-up preparation. The prepared material particle size distribution is 0.5-2μm, and has a high specific surface area.
[0039] The present invention utilizes inorganic metal halide clusters in the Cu(Ⅰ)MOFs framework to fix silver ions, and in situ forms AgX / Ag heterostructured nanoparticles in the framework pore structure, the particle size distribution of which is uniform, and the uniform distribution and particle size of the inorganic particles in the framework structure can be regulated by controlling the amount of silver ions introduced; the confinement effect of the framework structure avoids the agglomeration of nano AgX / Ag particles, thereby improving the stability of the material.
[0040] The present invention prepares a novel Cu(Ⅰ)MOFs-AgX / Ag nanomaterial with broad-spectrum bactericidal and antiviral properties. The material has excellent antibacterial properties and exhibits excellent antibacterial and antiviral effects on Staphylococcus aureus and Escherichia coli.
[0041] The present invention utilizes the systematic antibacterial and antiviral properties of Cu(Ⅰ)MOFs semiconductor and AgX / Ag nanoparticles and the light response characteristics of MOFs materials to further enhance the catalytic bactericidal effect of the composite material under light conditions, especially showing an enhanced killing effect on bacteria and viruses under light conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 X-ray diffraction patterns of the products prepared in Examples 1-3;
[0043] Figure 2This is a scanning electron microscopic image of the Cu(Ⅰ)MOFs prepared in Example 1;
[0044] Figure 3 The scanning electron microscope energy spectrum element analysis results of the Cu(Ⅰ)MOFs prepared in Example 1;
[0045] Figure 4 The scanning electron micrographs of the Cu(I)MOFs-AgCl / Ag nanomaterials prepared in Examples 1-3, wherein (a), (b) and (c) correspond to the products prepared in Example 1, Example 2 and Example 3, respectively;
[0046] Figure 5 Transmission electron microscopic images of the Cu(I)MOFs-AgCl / Ag nanomaterials prepared in Examples 1-3, wherein (a), (b) and (c) correspond to the products prepared in Example 1, Example 2 and Example 3, respectively;
[0047] Figure 6 The minimum inhibitory concentration test results of Cu(Ⅰ)MOFs and product Cu(Ⅰ)MOFs-AgCl / Ag nanomaterials prepared in Examples 1-3;
[0048] Figure 7 The pictures of the inhibition zone test of Cu(Ⅰ)MOFs and product Cu(Ⅰ)MOFs-AgCl / Ag nanomaterials prepared in Examples 1-3 against Staphylococcus aureus and Escherichia coli under light and dark conditions;
[0049] Figure 8 This is the measurement curve of the inhibition zone diameter of Escherichia coli under light and dark conditions for the Cu(I)MOFs prepared in Examples 1-3 and the product Cu(I)MOFs-AgCl / Ag nanomaterials. DETAILED DESCRIPTION
[0050] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention shall not be limited thereto.
[0051] The "ranges" disclosed herein are in the form of lower limits and upper limits. There can be one or more lower limits, and one or more upper limits, respectively. A given range is defined by selecting a lower limit and an upper limit.
[0052] The lower limit and upper limit of a particular range are defined. All ranges that can be defined in this way are inclusive and combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, a range of 60-120 and 80-110 is listed for a particular parameter, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range 3, 4 and 5 are listed, the following ranges can all be expected: 1-2, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0053] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0054] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0055] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0056] The preferred implementation methods of the present invention will be described in detail below in conjunction with specific embodiments. However, it should be understood that those skilled in the art can make reasonable changes, improvements and combinations to these embodiments without departing from the scope defined in the claims, so as to obtain new specific implementation methods. These new specific implementation methods obtained by changes, improvements and combinations are also included in the protection scope of the present invention.
[0057] Unless otherwise specified in the following examples, the reagents used may be commercially available products that can be routinely purchased by those skilled in the art, and the methods used may be conventional means in the art.
[0058] Example 1
[0059] (1) Preparation of Cu(Ⅰ)MOFs materials:
[0060] 1) Take cuprous chloride as an example and 4,4'-bipyridine (bpy) molecules as the raw materials for synthesizing MOFs, the solvent is acetonitrile, 5mmol of cuprous chloride precursor is added to 50mL of acetonitrile, and magnetic stirring is performed at room temperature for 10min;
[0061] 2) Dissolve 5 mmol of 4,4'-bipyridine molecules in 10 mL of acetonitrile, add to the copper salt solution after complete dissolution, and continue stirring for 30 min;
[0062] 3) After the reaction, the MOFs solid was separated by centrifugation at 7000 rpm for 10 min, and then washed twice by centrifugation with anhydrous ether. After vacuum drying at 60°C for 24 h, the Cu(Ⅰ)MOFs material was obtained.
[0063] Attached Figure 1-3 As a result of material characterization, the obtained Cu(Ⅰ)MOFs material has crystalline characteristics, with a morphological size distribution of 0.5-2μm, and the ratio of copper and halogen atoms in the inorganic cluster components in the skeleton is close to 1:1.
[0064] (2) Preparation of Cu(Ⅰ)MOFs-AgCl / Ag:
[0065] 1) Using silver nitrate as a silver ion source, 10 mg of silver nitrate was weighed and dissolved in 15 mL of anhydrous ethanol to prepare a silver nitrate ethanol solution;
[0066] 2) Weigh 50 mg of the prepared Cu(Ⅰ)MOFs material and add it to the above ethanol solution. After ultrasonic dispersion, magnetic stirring is performed for 1-12 hours. In this embodiment, the preferred stirring time is 12 hours.
[0067] 3) After the reaction, the sample was separated by centrifugation and washed twice with ethanol, and dried at 60° C. under vacuum conditions to finally obtain the Cu(Ⅰ)MOFs-AgCl / Ag material.
[0068] Attached Figure 1 When the composite Ag:Cu ratio is 0.25, the XRD of Cu(Ⅰ)MOFs-AgCl / Ag material shows the MOFs crystal structure, with the presence of AgCl and weak metallic Ag diffraction peaks; Figure 4 (a) and Figure 5 (a) Shows AgCl / Ag nanoparticles in the composite material.
[0069] (3) Antibacterial and antiviral performance test: Staphylococcus aureus and Escherichia coli were used as test bacteria, and the antibacterial performance of the material was characterized by the typical minimum inhibitory concentration (MIC), as follows: Use a 96-well plate, add 100 μL of Luria Bertani medium to each well except the first well; mix a certain concentration of the sample to be tested in the first well, and aspirate 100 μL from the first well to the second well, and so on until the tenth well, aspirate 100 μL; add bacteria (adding bacteria 0.2%) and dilute 500 times, and finally aspirate 100 μL of bacteria and add it to the 96-well plate; add 100 μL of sterile distilled water to the 11th well as a negative control; inoculate 100 μL of bacterial solution to the 12th well as a bacterial growth control; illuminate for 10 minutes, 37°C, and culture for 12-16 hours. Result judgment: Compared with the negative control, if it is turbid or has precipitation, it is judged that there is bacterial growth; if the transparency is the same as the negative control, it is judged that there is no bacterial growth.
[0070] Cu(Ⅰ)MOFs had an inhibitory effect on Staphylococcus aureus and Escherichia coli, with a MIC concentration of 500μg / mL. When the composite Ag:Cu ratio was 0.25, the antibacterial effect of Cu(Ⅰ)MOFs-AgCl / Ag material was significantly improved, with a MIC value of 62.5μg / mL (see Appendix Figure 6 ).
[0071] (4) Paper diffusion method to test the photocatalytic antibacterial performance: Staphylococcus aureus and Escherichia coli were used as test bacteria. The corresponding bacteria were first inoculated on the Luria Bertani culture medium with a sterile cotton swab. 4 mg of the material was weighed and dispersed in sterile water and placed on the culture medium inoculated with bacteria; kanamycin and sterile water were used as positive and negative controls; the samples were cultured at 37°C in the dark and under light conditions for 24 hours; the diameter of the inhibition zone was tested to determine the antibacterial performance of the material.
[0072] When the composite Ag:Cu ratio was 0.25, the Cu(Ⅰ)MOFs-AgCl / Ag material showed obvious photocatalytic antibacterial and antiviral effects on Escherichia coli, and the inhibition zone under light conditions was slightly larger than that under dark conditions (see Appendix Figure 7 and 8 ).
[0073] Example 2
[0074] The similar steps of Example 1 were repeated to prepare the Cu(Ⅰ)MOFs-AgCl / Ag antibacterial and antiviral material from the following raw materials. The amount of silver nitrate added in step (2) 1) was 40 mg, and the molar amount of silver ions was approximately 1:1 with respect to cuprous ions in Cu(Ⅰ)MOFs.
[0075] Attached Figure 1When the composite Ag:Cu ratio is 1.0, the XRD of Cu(Ⅰ)MOFs-AgCl / Ag material retains the MOFs crystal structure to a certain extent, and there are diffraction peaks of AgCl and enhanced metal Ag; Figure 4 (b) and Figure 5 (b) Showing the AgCl / Ag nanoparticles in the composite material.
[0076] When the composite Ag:Cu ratio was 1.0, the Cu(Ⅰ)MOFs-AgCl / Ag material had different inhibitory effects on Staphylococcus aureus and Escherichia coli, and the inhibitory effects were significantly improved, with MIC values of 31.3μg / mL and 15.6μg / mL, respectively (see Appendix). Figure 6 ).
[0077] When the composite Ag:Cu ratio was 1.0, the Cu(Ⅰ)MOFs-AgCl / Ag material showed obvious photocatalytic antibacterial and antiviral effects on Escherichia coli, and the inhibition zone under light conditions was significantly larger than that under dark conditions (see Appendix Figure 7 and 8 ).
[0078] Example 3
[0079] The similar steps of Example 1 were repeated to prepare the Cu(Ⅰ)MOFs-AgCl / Ag antibacterial and antiviral material from the following raw materials. The amount of silver nitrate added in step (2) 1) was 80 mg, and the molar ratio of silver ions to cuprous ions in Cu(Ⅰ)MOFs was approximately 2:1.
[0080] Attached Figure 1 When the composite Ag:Cu ratio is 2.0, the XRD of Cu(Ⅰ)MOFs-AgCl / Ag material retains the MOFs crystal structure to a certain extent, and the diffraction peaks of AgCl and metallic Ag are further enhanced; Figure 4 (c) and Figure 5 (c) Showing the AgCl / Ag nanoparticles in the composite material.
[0081] When the composite Ag:Cu ratio was 2.0, the Cu(Ⅰ)MOFs-AgCl / Ag material had different inhibitory effects on Staphylococcus aureus and Escherichia coli, and the inhibitory effects were significantly improved, with MIC values of 15.6μg / mL and 7.8μg / mL, respectively (see Appendix). Figure 6 ).
[0082] When the composite Ag:Cu ratio was 2.0, the Cu(Ⅰ)MOFs-AgCl / Ag material showed obvious photocatalytic antibacterial and antiviral effects on Escherichia coli, and the inhibition zone under light conditions was significantly larger than that under dark conditions (see Appendix Figure 7 and 8). Table 1 shows the energy spectrum element analysis results of the Cu(Ⅰ)MOFs-AgCl / Ag nanomaterials prepared in Examples 1-3. It can be seen that the Ag:Cu ratio of Example 1 is 0.25, the Ag:Cu ratio of Example 2 is 1.0, and the Ag:Cu ratio of Example 3 is 2.0.
[0083] Table 1 Spectrum element analysis results of the products Cu(Ⅰ)MOFs-AgCl / Ag nanomaterials prepared in Examples 1-3
[0084]
[0085] Example 4
[0086] The difference from Example 3 is that the halogen used is bromine, that is, the cuprous halogen compound is cuprous bromide, and the final material obtained is Cu(I)MOFs-AgBr / Ag, in which the molar amount of silver ions and cuprous ions in Cu(I)MOFs is approximately 2:1. The antibacterial effect is similar to that of the Cu(I)MOFs-AgCl / Ag material obtained in Example 3.
[0087] Example 5
[0088] The difference from Example 3 is that the halogen used is iodine, that is, the cuprous halogen compound is cuprous iodide, and the final material obtained is Cu(I)MOFs-AgI / Ag, in which the molar amount of silver ions and cuprous ions in Cu(I)MOFs is approximately 2:1. The antibacterial effect is similar to that of the Cu(I)MOFs-AgCl / Ag material obtained in Example 3.
[0089] Example 6
[0090] The difference from Example 1 is that in step (2) Cu(I)MOFs-AgCl / Ag preparation, the magnetic stirring time is 1 h.
[0091] Example 7
[0092] The difference from Example 1 is that in step (2) Cu(I)MOFs-AgCl / Ag preparation, the magnetic stirring time is 4 h.
[0093] Example 8
[0094] The difference from Example 1 is that in step (2) Cu(I)MOFs-AgCl / Ag preparation, the magnetic stirring time is 9 h.
[0095] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An AgX / Ag composite metal organic framework material, characterized in that: The material is Cu(Ⅰ)MOFs-AgX / Ag, where X is a halogen; Cu(Ⅰ)MOFs are assembled from cuprous metal-halogen ion clusters and 4,4'-bipyridine molecules, and silver ions are anchored by halogen ions to form Cu(Ⅰ)MOFs-AgX / Ag; In the Cu(Ⅰ)MOFs-AgX / Ag, the molar ratio of silver element to copper element is 0.25-2:
1.
2. The AgX / Ag composite metal organic framework material according to claim 1, characterized in that: The Cu(Ⅰ)MOFs-AgX / Ag particle size distribution is 0.5-2 μm.
3. A method for preparing the AgX / Ag composite metal organic framework material as described in any one of claims 1-2, characterized in that: The steps include: S1: MOFs preparation: S11: adding a cuprous halogen compound to a solvent and stirring at room temperature; S12: dissolving 4,4'-bipyridine molecules in a solvent, adding the 4,4'-bipyridine molecules to the solution obtained in step S11 after they are fully dissolved, and continuing to stir; S13: separating the MOFs solid in the solution obtained in step S12 by centrifugation, washing it by centrifugation with anhydrous ether, and vacuum drying it to obtain a MOFs material; S2: Preparation of Cu(Ⅰ)MOFs-AgX / Ag: S21: dissolving a silver ion source in anhydrous ethanol to form a silver ethanol solution; S22: weigh the MOFs material obtained in step S13 and add it to the silver ethanol solution obtained in step S21, disperse it by ultrasonic wave and then stir it; S23: The solid sample in the solution obtained in step S12 is centrifuged and washed by centrifugation with ethanol, and then vacuum dried to obtain Cu(Ⅰ)MOFs-AgX / Ag.
4. The method for preparing an AgX / Ag composite metal organic framework material according to claim 3, characterized in that: The cuprous halogen compound is selected from cuprous chloride, cuprous bromide or cuprous iodide; the solvent is acetonitrile; the cuprous halogen compound: 4,4'-bipyridine molecule: solvent = 5mmol: 5mmol: 60mL.
5. The method for preparing an AgX / Ag composite metal organic framework material according to claim 3, characterized in that: The stirring time in step S11 is 10 min; The stirring time in step S12 is 30 min; The centrifugal speed in step S13 is 7000 rpm, the time is 10 min, and the vacuum drying temperature is 60° C., the time is 24 h.
6. The method for preparing a AgX / Ag composite metal organic framework material according to claim 3, characterized in that: The silver ion source is silver nitrate; silver ion source: MOFs material: anhydrous ethanol = 10-80 mg: 50 mg: 15 mL.
7. The method for preparing an AgX / Ag composite metal organic framework material according to claim 3, characterized in that: The stirring time in step S22 is 1-12h; The vacuum drying in step S23 is carried out at a temperature of 60° C. and for a period of 24 hours.
8. Use of the AgX / Ag composite metal organic framework material as claimed in any one of claims 1 to 2 in the field of antibacterial and antiviral.
9. The use of an AgX / Ag composite metal organic framework material according to claim 8, characterized in that: Photocatalytic enhancement of antibacterial and antiviral effects of Cu(Ⅰ)MOFs-AgX / Ag.
Citation Information
Patent Citations
Silver-based metal organic framework material and preparation method and application thereof
CN112264103A
Composite catalytic material Cu@CN, preparation method and application
CN109908941A
Non-noble metal-MOFs (metal organic frameworks) composite as well as preparation method and application thereof
CN109912809A